The effects of trauma exposure and posttraumatic stress disorder (PTSD) on the emotion-induced memory trade-off - Mickley Steinmetz, Katherine R.; Scott, Laurie A.; Smith, David; Kensinger, Elizabeth A. (Frontiers in Integrative Neuroscience, 2012)
Many studies of memory changes in individuals with PTSD have focused on memory for trauma. However, it is unclear if these mnemonic differences extend beyond trauma memory to memory for other positive and negative information and if they are specific to individuals with PTSD or extend to other individuals who have experienced trauma. The present study examined the influences of trauma exposure and PTSD on an effect that may parallel tunnel memory in PTSD: the emotion-induced memory trade-off, whereby emotional aspects of an experience are remembered at the expense of the nonemotional context. Three groups (25 with current PTSD, 27 who had experienced trauma but did not have current PTSD, and 25 controls who had neither experienced significant trauma nor met criteria for current PTSD) were shown complex visual scenes that included an item (positive, negative, or neutral) placed on a neutral background. 45 minutes later, participants underwent a recognition memory test for the items and backgrounds separately. An emotion-induced memory trade-off was said to occur when there was a significant difference in item and background memory for emotional scenes, but not for neutral scenes. People with PTSD, like the other groups, were more likely to remember positive and negative items than neutral items. People with PTSD exhibited a memory trade-off, but this trade-off was no larger than for the non-trauma control group. Trauma-exposed people without a current diagnosis of PTSD did not show a trade-off, because they remembered the items within scenes better than their contexts even for neutral scenes. These results suggest that i) the effect of emotion on memory for visual scenes is similar in people with PTSD and control participants, and ii) people who have experienced trauma, but do not have PTSD, may have a different way of attending to and remembering visual scenes, exhibiting less of a memory trade-off than either control participants or people with PTSD.